Epstein–Barr Virus-Positive T/NK-Cell Lymphoproliferative Disorders Manifested as Gastrointestinal Perforations and Skin Lesions: A Case Report. Issue 5 (February 2016) - Xiao, Hai-Juan; Li, Ji; Song, Hong-Mei; Li, Zheng-Hong; Dong, Mei; Zhou, Xiao-Ge
Abstract : Abstract: Systemic Epstein–Barr virus (EBV)-positive T-cell lymphoproliferative disorders (LPDs) of childhood is a highly aggressive EBV-positive T/natural killer (NK)-cell LPD, which emerges in the background of chronic active EBV infection (CAEBV) or shortly after primary acute EBV infection. The clinical presentations of CAEBV are varied; patients with atypical manifestations are easily misdiagnosed. We described a 14-year-old boy suffering from digestive disorders and intermittent fever for 1 year and 9 months, whose conditions worsened and skin lesions occurred 2 months before hospitalization. He was diagnosed as inflammatory bowel diseases (IBD) and treated accordingly. His other clinical features, hepatosplenomegaly, lymphadenopathy, anemia, hypoalbuminemia, and elevated inflammatory marks, were found in hospitalization. The boy suffered from repeatedly spontaneous intestinal perforations shortly after hospitalization and died of intestinal hemorrhea. The pathological results of intestine and skin both showed EBV-positive T/NK-cell LPD (lymphoma stage). There are rare studies reporting gastrointestinal perforations in EBV-positive T/NK-cell LPD, let alone repeatedly spontaneous perforations. Based on the clinical features and pathological results of this patient, the disease progressed from CAEBV (T-cell type) to systemic EBV-positive T-cell LPD of childhood (lymphoma). Not all the patients with CAEBV could have unusual patterns of anti-EBV antibodies. However, the presence of high EBV loads (EBV-encoded early small ribonucleic acid (RNA) (EBER) in affected tissues and/or EBV deoxyribonucleic acid (DNA) in peripheral blood) is essential for diagnosing CAEBV. Maybe because of his less common clinical features for CAEBV and negative anti-EBV antibodies, the boy was not diagnosed correctly. We should have emphasized the test for EBER or EBV-DNA. Meanwhile, for the IBD patients whose manifestations were not typical, and whose conditions were not improved by suitable therapies against IBD, infectious and malignant diseases should be considered.